ASSESSING THE PREVALANCE OF PAIN AND THE EFFICACY OF PAIN MANAGEMENT FOR HOSPITALIZED ELDERLY PATIENTS IN INTERNAL MEDICINE DEPARTMENT OF THONG NHAT HOSPITAL - Thắm, Đỗ Thị; Vân, Hoàng Ngọc; Trang, Nguyễn Thùy; Sự, Nguyễn Đức (Journal of Health and Aging, 2025)
We conducted this study to assess the prevalance of pain and the efficacy of pain management for hospitalized elderly patient in Internal Medicine Department of Thong Nhat hospital from 4/2024 to 7/2024. Cross-sectional study at two time points 246 of eligible hospitalized elderly patients were assessed for pain by using the Vietnamese version of Brief Pain Inventory short form. Patients who experienced pain were then re-assessed again after 7 days by using the same measurement tool. Besides, data on demographic factors clinical characteristics and medication use were collected from medical records during the last days. The prevalance of pain among 246 hospitalized elderly patients was relatively high at 51.22% and significantly related to injuries (p < 0.001), musccular- skeletal disorder (p < 0.0001), surgical disease (p= 0.023). The common locations of pain were leg, head, abdomen and back. Among patient with pain, the median score of worst pain, the average pain and the interview pain was 7.3±1.86; 5.18 ± 1.83; 4.91± 2.27 ( on a scale from 0 to 10). Pain affected all daily activities of elderly patients, 65.9 % patients with pain experience serve pain related interference. 71.4% of hospitalized elderly patients with pain reported therapeutic efficacy (cut off as 50% of pain reduction). A large portion of patients were treated by using acetaminophen (69.8%), topical pain relief (33%), antiepileptic drugs (31.7%), NSAID (13.5%), morphin (0.8%). Pain is a common problem with high intensity and severe impairment of daily activities in hospitalized elderly patients, significantly related to injuries, musccular- skeletal disorder, surgical disease. Result of this study emphasizes the role of appropriate pain asessment and management to improve the treatment effectiveness and the quality of life of elderly patients.